Student Attendance Information System Using QR Code (Quick Response) At ITSNU Kalimantan - Liyando Hermawan Hasibuan; Achmad Arif Munaji; Agatha Deolika; Nadya Chitayae; Erik Setiawan (JURNAL SISFOTEK GLOBAL, 2022)
In this increasingly advanced era, Information Technology (IT) is unavoidable. Everyone is competing to find innovations that can improve their performance. Private Universities (PTS) in Indonesia are no exception. An educational institution's attendance list is the primary reference in monitoring student activities. Although this sector is critical, traditional data collection is still taking place. As a result, many problems arise, such as data loss, long charging times, long queues, overcrowding, and even affects student concentration. ITS NU Kalimantan is one of several private universities in Central Kalimantan and is still relatively new. Student attendance applications are designed and developed for more mature data collection to avoid problems that arise later. This study offers the use of web android-based technology equipped with a QR code feature. Based on the questionnaire results conducted on 45 respondents who used the UAT model, the perceived usefulness aspect was 82%, the perceived ease of use aspect was 84%, the perceived user acceptance aspect was 82%, and the average rating produced was 83%. This percentage shows that users respond positively to this attendance system.